METHODS OF TEACHING UKRAINIAN PROFESSIONAL VOCABULARY FOR FUTURE DOCUMENTOLOGISTS - Reshetilova О. М. (Continuing Professional Education: Theory and Practice, 2023)
The article has perfectly described and defined the basic characteristics of the main methods of teaching of Ukrainian professional vocabulary for future documentologists according the existing of high school. It’s been analyzed a variety of interpretations of scientific approaches for the definition of «The methods of teaching». Special attention is given to promising methods of teaching: verbal presentation of the teacher (story, explanation, lecture), conversation, working with a textbook (including electronic ones) observation and analysis of linguistic phenomena, a method of exercises, programmed teaching and interactive methods. The author of the article notes that these methods correspond to the basic directions of work in the high level of education, thy let to organize the process of educating for documentologists in Ukrainian professional vocabulary according the logical structure, also they provide teacher’s relationship with students during the work in language material, and they give the possibilities to use different levels of the learning activities of students. Rather big attention is paid to the method of exercises that has the great importance for the development of the processes of perception, reconstruction and production of the oral and written speech by the students, which provides the masterskills of using the Ukrainian vocabulary by the students in this department. The article states, that the choosing of the methods of the teaching of the Ukrainian professional vocabulary for the students can’t be arbitrary, because it depends on many objective factors. Choosing the method or technique of teaching of the Ukrainian professional vocabulary for documentologists, the teacher must pay attention for their didactic, developmental potential, and on emphasizing development of the range of Ukrainian vocabulary